Distribution And Clinical Significance of Microdeletions in The AZF Region of The Y Chromosome in Male Infertility (Eurasian Medical Research Periodical, 2026)
This article examines various types of microdeletions in the AZF region of the Y chromosome and their impact on male infertility. Particular attention is given to the prevalence of AZF microdeletions among patients with azoospermia and oligozoospermia, as well as their clinical manifestations. Data are presented on the prevalence of AZFa, AZFb, and AZFc microdeletions and their effects on male reproductive function. The primary focus is on the pathogenesis, molecular mechanisms, and diagnosis of these abnormalities. For each type of microdeletion, clinical features, diagnostic methods, and treatment approaches using assisted reproductive technologies are described